What Can We Learn from the ELPSA, SA, and PSA Frameworks? The Experience of SEAQiM - Fadjar Shadiq (Southeast Asian Mathematics Education Journal, 2017)
One of education problems in Indonesia according to Dr. Anies Baswedan, the former Minister of Education and Culture of the Republic of Indonesia, was: “How to help Indonesian students to be independent learners and have good characters?” This question then raises an issue: “What kinds of knowledge, skills, and attitudes are needed by our students to survive in the 21st Century and beyond?” Earlier the author stated (Shadiq, 2016a) that to change and improve the quality of the teaching and learning process from a ‘typical’ or ‘traditional’ mathematics classroom to a more innovative one was not easy. Afurther issue was: “How to change real teaching practice?” Mathematics teachers need to experience ways that they will be expected to implement in their teaching. Isoda (2011) proposed a Problem Solving Approach (PSA) which consists of four steps: (1) problem posing, (2) independent solving, (3) comparison and discussion, and (4) summary and integration. In Indonesia, we can learn from Scientific Approach (SA) which covers five steps: (1) observing, (2) questioning, (3) collecting data or experimenting, (4) reasoning, and (5) communicating. In addition, Lowrie and Patahuddin (2015) proposed Experiences, Language, Pictures, Symbols, Application (ELPSA) as a lesson design framework for mathematics teaching and learning process. A problem is examined based on these three frameworks where at least 11 alternatives can be identified to solve it. The paper ends with some recommendations on how to improve Indonesian mathematics teaching.